Studi Perilaku Harian Anak Lutung Jawa (Playgroup) Di Pusat Rehabilitasi Lutung Jawa - Kurniawan, Iwan; Kusumawardani, Niniek Dyah; Taegusman, Eugenius (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Research objectives for knowing the daily behavior patterns of jouvenile (playgroup) at the Javan Langur Rehabilitation Center. The research was carried out at the Javan Langur Rehabilitation Center,Coban Talun, Tulungrejo Village, Bumiaji District, Batu City, East Java in May - June 2024. The tools used are writing instruments, cameras, watches and data tables field. The research object is four jouvenile individuals (playgroup) consisting of three jouvenile langur aged 11 months and one jouvenile langur aged 11 months one year. The direct observation method is used in research for knowing the daily behavior patterns of jouvenile langur (playgroup). Procedure data collection using scan sampling technique. Daily behavior recording jouvenile langur using continuous recording techniques. Behavioral parameters Observed daily activities include moving (locomotion), resting, social, eating, drinking, urination, defecation, auto grooming. Total daily behavior of jouvenile Langurs is calculated using the activity percentage formula.The results of the research show the daily behavior of jouvenile langurs (playgroup) at the Javan Langur Rehabilitation Center is a resting behavior of 54.72%, eating behavior 41.98%, movement behavior 1.06%, social by 1.35%, drinking behavior by 0.43%, auto grooming behavior of 0.39%, urination behavior of 0.04%, defecation behavior of 0.03%.